Diagnosis of the Death from Hypothermia on Postmortem Imaging - Wenjing Gao; Wenju Jin; Jiahui He; Sunao Li; Long Fu; Zhiyuan Xia; Haibin Shen (Journal of Forensic Science and Medicine)
Background: Diagnosis of fatal hypothermia is challenging by autopsy approach alone. Aims and Objectives: To explore the features of fatal hypothermia on postmortem computed tomography (PMCT) and study their diagnostic value in such cases. Materials and Methods: A retrospective study was conducted on the imaging data of three cases of low-temperature death. The study compared the images of lung tissue in the control group and used statistical tools to analyze typical changes associated with low-temperature death. The potential applications of cadaveric imaging in these cases were also discussed. Results: The typical postmortem imaging manifestations of death from hypothermia include increased volume of bilateral lung tissue, decreased density of bilateral lung tissue, and absence of pulmonary hypostasis. By comparison, it has been proven that PMCT can quickly detect typical changes in postmortem imaging of death from hypothermia. After applying PMCT, combined with the results of postmortem imaging, physical and chemical, and the environmental condition of the scene, in the absence of individual deaths because of other reasons, it can be determined that the individual died from hypothermia. Conclusions: The case of the death from hypothermia is a tough issue in forensic pathology examination. Through this review, it was found that the death from hypothermia cases have typical postmortem imaging. After combining the case, on-site investigation, and toxicology testing, we found the PMCT can solve the case of the death from hypothermia.